Sources of Geographic Variation in Health Care: Evidence From Patient Migration. (19th July 2016) - Finkelstein, Amy; Gentzkow, Matthew; Williams, Heidi
Abstract: We study the drivers of geographic variation in U.S. health care utilization, using an empirical strategy that exploits migration of Medicare patients to separate the role of demand and supply factors. Our approach allows us to account for demand differences driven by both observable and unobservable patient characteristics. Within our sample of over-65 Medicare beneficiaries, we find that 40–50% of geographic variation in utilization is attributable to demand-side factors, including health and preferences, with the remainder due to place-specific supply factors.